STRATEGIES FOR DEVELOPMENT OF SANTRIPRENEUR EDUCATIONAL MANAGEMENT IN IMPROVING SELF-LIVING CAPACITY - Abdul Aziz KM; Jajat S. Ardiwinata; Viena Rusmiati Hasanah (Jurnal Scientia, 2023)
The increase in potential depends heavily on the management development carried out by managers, educators, and educational personnel. The aim of the research is to know the development strategy of the management of the Santripreneur program on the Tahfidz Quran study group in improving the ability to live independently. Qualitative research carried out at the Rumah Tahfidz Quran Al Hanan, and the Pondok Pesantren Daarul Maghfiroh, was purposefully sampled as the subject of research. Data collection is carried out using observation, interview and documentation techniques. The strategy of capability development and the strategy of empowerment approach can be used as a strategy of approach in the development of entrepreneurial capabilities on the program of the entrepreneur through growing developing the potential of individuals and institutions. As for the management of the program can be done through the development of students, tutors, managers, means, facilities and funds of learning, learning process, and learning output